The Analisis Tindak Tutur Lokusi, Ilokusi, Perlokusi dalam Film Kukira Kau Rumah Karya Umay Shahab - Siti Ruqmana, Siti Ruqmana; Ahada Wahyusari, Ahada Wahyusari; Legi Elfitra, Legi Elfitra (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This research aims to describe the locutionary, illocutionary and perlocutionary speech acts in the film "Kukira Kau Rumah" by Umay Shahab. The method used by this research is descriptive with a qualitative approach. The instrument of this research is the research itself with a data analysis guideline table. The data collection techniques used in this research is listening and recording. The results obtained in this research is sixty locutionary speech act data, namely four statement locution data (declarative), ten question locution data (interrogative), six command locution data (imperative). Then, there are twenty-four illocutionary speech acts data, seven verdictive illocutionary data (verdictives), four exercive illocutionary data (exersitives), three commissive commissive illocutionary data (commissives), seven behabitive illocutionary data (behabitives), three expositive illocutionary data (expositives). Meanwhile, sixteen data for perlocution